Evaluating the effect of oil prices volatility on the capital expenditure of the Federal Government in Nigeria / Oluwagbade Isaiah Oluyinka, Efuntade Alani Olusegun and Efuntade Olubunmi Omotayo - Oluyinka, Oluwagbade Isaiah; Olusegun, Efuntade Alani; Omotayo, Efuntade Olubunmi (Universiti Teknologi MARA Selangor, 2023)
This study examines the effect of oil price volatility on federal government capital expenditure in Nigeria over the time frame from 1993 to 2022. The analysis was conducted using secondary data obtained from relevant government agencies. The study focuses on analysing the impact of volatility in the prices of Brent UK crude oil, OPEC spot rate crude oil, and West Texas intermediate crude oil prices on capital expenditure. It takes into account the potential disruptions caused by oil subsidies, corruption, and inflation. The study employed an ex-post facto research design via the autoregressive distributed lagged (ARDL) regression. The empirical findings of the model indicate that the volatility of Brent UK crude oil price, OPEC spot rate crude oil, and West Texas intermediate crude oil price volatility do not have a statistically significant effect on the federal government’s capital expenditure. This indicates that oil price volatility is a short-run phenomenon that will fade out in a short period, thus explaining the high speed of adjustment of the error correction term. There is a need to monitor the federal government’s capital expenditure pattern and the income of key revenue-generating agencies. The federal government should continue to prioritise fiscal reforms in order to create space for capital and infrastructural development.